Free Flap Reconstruction of Extremity Defects in Pediatric Patients - Li, Jin; Xiong, Hewei; Li, Gongchi; Zhou, Pan; Ai, Fangxin; Wang, Kun; Chen, Jianghai (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2021)
Background Microsurgical reconstruction of extremity defects with free flaps has been carried out for many years. The aim of this retrospective study is to characterize free flap surgery on children of 1 to 7 years old by evaluating a series of 20 cases of free flap surgeries that have been performed in pediatric patients.Methods From February 2014 to January 2018, 20 patients, 10 boys and 10 girls aged from 1 to 7 years (average, 4.6 years), were engaged in this study. Several types of free flaps were used, including anterolateral thigh flaps (ALT), inferior ulnar collateral artery flap, latissimus dorsi flap, medial plantar flap, fibular osteocutaneous flap and hallux toenail flap. After operations, follow-up period was at least for 2 years and the average follow-up period was 48.5 months. The long-term outcomes were estimated by questionnaires derived from the American Academy of Orthopaedic Surgeons Pediatric Outcomes Data Collection Instrument (PODCI).Results A total of 21free-flap reconstructions were performed on 20patients, including 15 ALT, 3 composite flaps, and 3 other cutaneous flaps. The size of the tissue flap ranged from 1.5 to 280 cm2 (average, 74.1cm2). The diameter of the anastomosed artery of the flap ranged from 0.7 to 1.2 mm. Among the 21 flaps, 20 survived and the success rate was about 95 %. Contour adaption was achieved in all flaps. Fifteen children received a secondary operation for debulking or functional improvement. Secondary deformity was present in 3 children, among which ankle joint valgus was seen in two children and a flexion deformity of injured toe occurred in one child. The mean global functioning score of PODCI was 94 (ranging from 81 to 98, maximum 100).Conclusion The success rate of free-flap surgery in pediatric patients was comparable to that achieved in adults. Post-operative caring for pediatric patients was easier than expected. For pediatric patients, the final outcomes were not varied remarkably from different types of free tissue transfer.
Keywords: Pediatric patients; tissue defect; free flap; long-term outcome